Communicating Hydrocarbons – Fuelling Conflict or Warming Relations: Media Representations of the Natural Gas Reserves in East Mediterranean - Çiftçioğlu, Vasvi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
The Mediterranean island of Cyprus, the last divided country in Europe, faced a grave risk of plunging into war in September 2011. The reason behind this danger was represented as the confrontation over the excavation of hydrocarbon reserves found in the Eastern Mediterranean Sea. A significant hydrocarbon field discovery like this, where it is said that the value of the reserves is around 100 billion Euro, might be a cause for great rejoicing anywhere else in the world, but here it further escalated the Cyprus conflict. This is a comparative study, based on quantitative content analysis that focuses on the coverage of the hydrocarbons conflict in all daily Turkish Cypriot and Greek Cypriot newspapers published in September 2011. The main goal of this thesis is to explore the extent to which peace journalism was practised, or not, by analysing the front-page stories of the Turkish Cypriot and Greek Cypriot newspapers about this conflict. This study employs critical communication research theories to critically contextualize its own findings in particular and the potential of media for practising Peace Journalism in general. Peace Journalism which become popular in the academic and professional arena during the last decade, challenges traditional journalism in several ways and offers brand new approaches for reporting local or international conflicts. A review of peace journalism research reveals that researchers have mainly focused on war reporting. In order to address this deficit in peace journalism research, this thesis focuses on a case study where there was a risk for military confrontation. The combined sample, 629 front page stories analysed for all 18 newspapers from both communities indicates a strong preference towards war journalism. The newspapers from both sides, failed to discuss peaceful solutions to the hydrocarbons conflict and they also failed to discuss negative repercussions of a possible war related to the hydrocarbons conflict. Keywords: Cyprus problem, peace journalism, war journalism, reconciliation, conflict reporting, hydrocarbons conflict, critical communication research

ÖZ: Avrupa'nın son bölünmüş ülkesi olan Akdeniz adası Kıbrıs, Eylül 2011'de ciddi bir savaş tehlikesi atlattı. Bu tehlikenin nedeni, Doğu Akdeniz'de bulunan hidrokarbon rezervlerinin çıkarılması konusunda yaşanan uzlaşmazlık olarak sunuldu. Değerinin 100 milyar Euro civarında olduğu söylenen böyle bir hidrokarbon keşfi, dünyanın başka herhangi bir yerinde büyük sevinç yaratabilecekken, burada halihazırda devam eden Kıbrıs sorununu daha da tırmandırdı. Bu tez, Eylül 2011'de yayınlanan tüm günlük Kıbrıs Türk ve Kıbrıs Rum gazetelerinin ön sayfalarında hidrokarbon krizine ilişkin haberlerin karşılaştırılmalı bir nicel içerik analizini yapıyor. Bu tezin temel amacı söz konusu hidrokarbon krizi sunulurken barış gazeteciliği yaklaşımının ne kadar kullanılıp kullanılmadığını ortaya çıkarmaktır. Bu çalışma, özellikle kendi bulgularını eleştirel bir bağlamda sunma, genelde ise barış gazeteciliğinin pratikte hayat bulma potansiyelini değerlendirmek için eleştirel medya kuramlarından faydalanmıştır. Son on yılda akademik ve profesyonel alanda popüler hale gelen Barış Gazeteciliği, geleneksel gazeteciliğe çeşitli şekillerde meydan okuyor ve yerel veya uluslararası çatışmaları haberleştirmek için yepyeni yaklaşımlar sunuyor. Barış gazeteciliği konusunda yapılan araştırmalara yakından bakınca, araştırmacıların ağırlıklı olarak savaşların haberleştirilmesi konusuna odaklandığını görülüyor. Barış gazeteciliği araştırmalarındaki bu açığı gidermek için, bu tez savaş riski taşıyan hidrokarbon uzlaşmazlığını kendine örnek olay olarak kullanıyor. Her iki toplumdan 18 gazetede yayınlanan toplam 629 ön sayfa haberini içeren örneklem üzerinde yapılan analizler, savaş gazeteciliği konusunda çok ağırlıklı bir tercih yapıldığını ortaya koyuyor. Her iki taraftan gazeteler, hidrokarbon uzlaşmazlığına barışçıl çözümler bulunmasını tartışamadığı gibi bu uzlaşmazlığın sıcak çatışmaya dönmesinin yaratacağı olumsuzlukları tartışma konusunda da yetersiz kaldı. Anahtar Kelimeler: Kıbrıs sorunu, barış gazeteciliği, savaş gazeteciliği, uzlaşma, uzlaşmazlık haberciliği, hidrokarbon uzlaşmazlığı, eleştirel iletişim araştırması
Doctor of Philosophy in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Communication And Media Studies, Dept. of Communication and Media Studies, 2020. Supervisor: Assoc. Prof. Dr. Mashoed Bailie.
Keywords: Communication and Media Studies; Natural gas--Economics--Cyprus; Petroleum--resource economics; Energy Economics--Mediterranean Region; Cyprus problem; peace journalism; war journalism; reconciliation; conflict reporting; hydrocarbons conflict; critical communication research